Thulium laser treatment for bladder cancer - Wang, Wei (Asian J Urol, 2016)
Recent innovations in thulium laser techniques have allowed application in the treatment of bladder cancer. Laser en bloc resection of bladder cancer is a transurethral procedure that may offer an alternative to the conventional transurethral resection procedure. We conducted a review of basic thulium laser physics and laser en bloc resection procedures and summarized the current clinical literature with a focus on complications and outcomes. Literature evidence suggests that thulium laser techniques including smooth incision, tissue vaporization, and en bloc resection represent feasible, safe, and effective procedures in the treatment of bladder cancer. Moreover, these techniques allow improved specimen orientation and accurate determination of invasion depth, facilitating correct diagnosis, restaging, and re-evaluation of the need for a second resection. Nonetheless, large-scale multicentre studies with longer follow-up are warranted for a robust assessment. The present review is meant as a quick reference for urologists.